Стратегія взаємодії промислового підприємства на засадах маркетингу партнерських відносин. - Куваєва, Тетяна Володимирівна (Національний технічний університет «Дніпровська політехніка», Дніпро, 2018)
Дисертацію присвячено обґрунтуванню теоретично-методичних засад і розробці практичних рекомендацій щодо формування маркетингової стратегії взаємодії промислового підприємства на засадах партнерських відносин. Систематизовано основні підходи до формування стратегії взаємодії на основі маркетингу партнерських відносин. Удосконалено науково-методичні підходи до формування маркетингової стратегії взаємодії підприємств на основі партнерських відносин, до оцінювання впливу маркетингових стратегій взаємодії споживача-постачальника на організацію їхньої діяльності, а також до прогнозування зміни форми стратегій взаємодії. Доведена доцільність виділення підприємства-інтегратора з числа учасників партнерства, визначено його роль та функції. Обґрунтовано методичний підхід до оцінювання

Диссертация посвящена разработке теоритико-методических основ и практических рекомендаций по формированию маркетинговой стратегии промышленного предприятия на основе партнерских отношений. Систематизированы основные подходы к формированию стратегий взаимодействия на основе маркетинга партнерских отношений. Усовершенствованы научно-методические подходы к формированию стратегии взаимодействия предприятий на основе партнерских отношений, к оценке влияния маркетинговых стратегий взаимодействия потребителя-поставщика на организацию их деятельности, а также к прогнозированию изменения формы стратегий взаимодействия. Доказана целесообразность выделения предприятия- интегратора из числа участников партнерства, определена его роль и функции. Обоснован методический подход к оценке целесообразности взаимодействия промышленного предприятия в партнерстве.

The thesis is devoted to the substantiation of theoretical and methodological principles and the development of practical recommendations on the formation of a marketing strategy for the interaction of an industrial enterprise on the basis of partnership. The approaches to the formation of enterprise interaction strategy in the supply and distribution channels are systematized. It is established that at the present stage of marketing development, the most dynamic development is observed in partnership marketing for it allows providing long-term interaction of enterprises, minimizing the risks of their activities and adapting to external changes. There is proposed a classification of approaches to the formation of the interaction strategy of an industrial enterprise on the basis of partnership marketing, which additionally takes into account the degree of interdependence of enterprises in the supply and distribution channel. There has been improved the scientific and methodological approach to the formation of a marketing strategy of enterprises interaction on the basis of partnership under network business organization. There is proved the necessity of taking into account the key attributes of differentiated goods and the specifics of emergence of their needs in the formation of interaction strategy of an industrial enterprise. There has been substantiated the scientific and methodological approach to quantitative estimation of influence of marketing strategies of enterprises interaction on organization of their activity. It has been established that environmental factors and attributes of differentiated goods determine the probabilistic nature of the rise of demand for goods and increase in the risk of empty or else overloaded storage facilities at the consumer of such goods. It is proved that the application of the marketing strategy of in-depth flexible partnership allows: for the consumer – reducing the critical stock almost twice and the maximum capacity of the warehouse in comparison with transaction marketing; and for the manufacturer – significantly reducing the peak load of the equipment and the maximum required capacity of the warehouse. There is developed the methodological approach to forecasting the changes in the marketing strategy of interaction between the consumer and the supplier through the calculation of the density of the integrated flow of events. It is proved that the development of marketing relations between enterprises in the supply and distribution channels of industrial products can be predicted on the basis of a model in which the transitions between states (strategies) such as: lack of marketing relationships, transaction marketing, initial partnership and deepened flexible partnership – are influenced by the flow of events that accompany the interaction of the enterprise. There is substantiated the order of determining the density of events that lead to changes in marketing strategy of consumer-supplier interaction. It is substantiated that the formation of the model of managing the interaction in industrial partnerships should be based on determining the integrator-enterprise among the members of the supply and distribution channel. Such an enterprise should have the maximum degree of influence on other companies of the supply and distribution channel. The role and functions of the integrator-enterprise in the model of interaction management in partnership are determined. Such an enterprise is a member of the channel and has the greatest specific weight of all direct and indirect relationships in it. The main functions of the integrator-enterprise are as follows: conducting descriptive marketing research in order to identify the external factors that affect the formation of the interaction strategy between enterprises, and analysis of the effectiveness of their partnership. This allows for additional benefits for partners. The methodological approach to assessing the expediency of partnership interaction of an industrial enterprise is substantiated, and practical recommendations for the formation of a marketing strategy for industrial enterprise interaction with partners are developed. It is proved that assessment of expediency of realizing the strategy of enterprise interaction on the basis of partnership marketing should be based both on consideration of the effectiveness of the partnership (by calculating the integral indexes by groups of motives, in particular, production, logistics, marketing, etc.) and indexes of relationship between participants (by calculating the arithmetic mean value of the expert evaluation of certain relationship characteristics). This allows one to justify the further marketing strategy of participation in the partnership. The substantiated scientific and methodological approach to forming the strategy of interaction with suppliers has been tested at the “Pivdenukrgeologia” Communal Enterprise by determining the expediency of establishing a partnership with the integrator-enterprise defined.
Стратегия взаимодействия промышленного предприятия на основе маркетинга партнерских отношений.
Interaction strategy of an industrial enterprise on the basis of partnership marketing
Keywords: промислове підприємство; промышленное предприятие; industrial enterprise; стратегия взаимодействия; стратегія взаємодії; interaction strategy; маркетинг партнерських відносин; маркетинг партнерских отношений; partnership marketing; підприємство-інтегратор; предприятие-интегратор; partnership marketing; поглиблене гнучке партнерство; углубленное гибкое партнерство; in-depth flexible partnership